Value Relevance of Information Disclosure: A Case Study of Companies Listed in LQ45 Index of Indonesian Stock Exchange in Period 2016 - 2017 - Khoifin, Kiki; Bungkilob, Dej-anan (International Journal of Psychosocial Rehabilitation, 2020)
Challenges will always exist and be undeniable on the stock exchange. Providing high-quality information disclosure and transparency is one of the challenges required by investors for assessment purposes and better economic decision-making. For the sake of boosting the information disclosure and transparency issue among Publicly Listed Companies (PLCs), Indonesia has released act of directors of Jakarta Stock Exchange No. Kep-306/BEJ/07-2004 and act of Financial Service Authority or Otoritas Jasa Keuangan (OJK) No.KEP-134/BL/2006. The regulations have significantly contributed to improving the information disclosure and transparency, which was revealed by the report of the Asian Development Bank in 2015. The report showed the increase in scores from 13.43 points in 2012 to 17.50 points in 2015, or a 30.31% improvement. However, the score is still lower than its neighboring countries, such as Malaysia (18.86 points), Thailand (20.07 points), and Singapore (19.06 points). Nevertheless, queries have been rising from researchers as to whether information disclosure has value relevance for investors. In responding to the question, understanding the value relevance is necessary to be delivered. Value relevance is the ability of accounting numbers to summarize the information underlying the stock price; hence, value relevance is designated by a statistical association between financial information and price or return. Therefore, this study aims to investigate whether information disclosure consists of financial statements and voluntary disclosure of the companies that were listed in the LQ45 index on IDX in the period 2016-2017 and have value relevance. The most significant result found that financial statements represented by BVPS and EPS have value relevance. This study has implications and is useful for readers due to the information preparation. The listed companies will gain knowledge of the extent, type, and amount of information that should be disclosed in order to be successful in attracting investors to source funds on the stock exchange. The finding is beneficial for future literature regarding accounting information and contribution to investors in weighting which information is the most concerned for assessment.